Barriers or Catalysts? Traditional Institutions and Social Mobility in Rural India - Vegard Iversen; Anustup Kundu; Rahul Lahoti; Kunal Sen (Institute of Labor Economics (IZA), 2023)
We examine how village level social group dominance affects the educational and occupational mobility of minority and other social groups in rural India across multiple generations. Theoretically, we distinguish between upper caste and own group dominance and examine the mechanisms underpinning inequality in mobility outcomes. We find inequality in upward educational mobility to have significantly narrowed over time with SCs doing better in upper caste and own-dominated villages, while STs and Muslims do worse in own-dominated villages. In contrast, for occupational mobility, we find no evidence of minority groups catching up with upper castes while SCs and STs are particularly disadvantaged, but SCs, again, do comparatively better in their own dominated villages. Exploring the mechanisms that explain the relationships between land dominance regimes and mobility, we find that a combination of agroecological and natural resource base and social cohesion of villages underpin the differences observed more than public goods provision. Our findings suggest a new pattern of inequality where historically disadvantaged groups appear less able to convert educational gains into labour market and occupational progress.
Keywords: J62; J71; O12; 330; educational mobility; occupational mobility; caste; village dominance regimes; India